Photovoltaic system for maximum power point tracking using hybrid firefly and perturbation and observation algorithm - Lavety Navinkumar Rao; Rahul Somalwar; Harshit Dalvi; Satyavir Singh; Partha Sarathi Subudhi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This work presents the novel maximum power point tracking (MPPT) approach for a small 50 W photovoltaic (PV) system using the dc-dc converter. The method of modeling of PV module is discussed. The firefly (FFY) algorithm and the perturbation and observation (P&O) algorithm are combined to implement MPPT of the PV system connected to battery load. The operating principle is discussed in detail and steady-state analysis of the proposed system is implemented through simulation. The charging profile of the 7.5 Ah VRL battery is also studied using simulation. Furthermore, a low-cost microcontroller-based experimental setup rated at 50 W system connected to battery load was built to implement a hybrid FFY-P&O algorithm. The experimental results are in same as the simulation result. In contrast to the traditional P&O approach, it demonstrated the quick and efficient maximum power point operation triggered by a sudden transition in the environment.